2021
DOI: 10.1186/s12917-021-02932-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary Chlorella vulgaris and carbohydrate-active enzymes incorporation on plasma metabolites and liver lipid composition of broilers

Abstract: Background Chlorella vulgaris has been proposed as a sustainable green feedstock in poultry nutrition due to its ease of cultivation, minimal environmental impact and balanced nutritional composition. However, the majority of studies documents the use of C. vulgaris as a dietary supplement in broilers instead of a feed ingredient. To the best of our knowledge, no report has shown the effect of a high-level incorporation (>2 % in the diet) of C. vulgaris on plasma metabolites and hepatic lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
(69 reference statements)
5
11
0
Order By: Relevance
“…The present study highlights cholesterol- and lipid-lowering properties of individual L. digitata , although the mechanism of this hypocholesterolaemic action is still unclear. As previously observed for some microalga species [ 29 ], this improved effect on lipemia upon supplementation with L. digitata can be attributed to a decrease in intestinal tract fat absorption [ 26 ]. Glucose was slightly increased in L. digitata fed broilers, independently of the addition of feed enzymes.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The present study highlights cholesterol- and lipid-lowering properties of individual L. digitata , although the mechanism of this hypocholesterolaemic action is still unclear. As previously observed for some microalga species [ 29 ], this improved effect on lipemia upon supplementation with L. digitata can be attributed to a decrease in intestinal tract fat absorption [ 26 ]. Glucose was slightly increased in L. digitata fed broilers, independently of the addition of feed enzymes.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, feeding brown macroalga Hizikia fusiformis by-products [ 24 ] and a purified polymannuronate from a brown alga mix [ 25 ] at 0.4 to 0.5% feed led to an increase of feed efficiency. It also should be underlined that the percentage of L. digitata incorporation in the diet and the duration of the experimental period impact broilers’ growth performance parameters [ 26 ]. In the present study, similarly to what was previously reported for polymannuronate polymer of alginate used as a feed supplement for broilers [ 25 ], the dietary supplementation with the in vitro selected alginate lyase [ 17 ] was expected to release bioactive polysaccharides from L. digitata cell wall, such as alginate, with prebiotic activity and, consequently, improve broiler performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations